TARUNA: Transformation of Strengthening Religious Cultural Construction at State Vocational High School 1 Geger Madiun - Sugiyar, Sugiyar (Didaktika Religia, 2023)
This research focuses on the transformation of strengthening the religious culture construction of State Vocational High School 1 Geger Madiun. The purpose of the research is to explain the position and important role of TARUNA in the formation of a superior generation with skills and noble character in vertical and horizontal relations. TARUNA is an educational and training activity for students in vocational high schools. Vocational high schools are synonymous with strengthening the field of expertise and skills. Strengthening the construction of religious culture is an integral part of forming a superior person. A superior person has skills and a good spiritual and social foundation. Data collection methods were carried out by observation, interview, and documentation. Data were obtained from several informants, namely: principals, teachers, education personnel, and students. The interactive analysis model was used to analyze the data with steps, including: data collection, data condensation, data presentation, and conclusion. The study results show that: (1) TARUNA is a means to build the physical toughness of students as a preparation for a strong and resilient person in the world of work; (2) TARUNA builds the spirituality of students to realize personal piety with religious behavior and noble morals; and (3) The construction of a religious culture can be realized by combining spiritual piety, social piety, and qualified skills, so that it becomes a model of religious culture in vocational schools.